When self-help materials help: Examining the effects of self-discrepancy and modes of delivery of positive self-statements. Issue 2 (3rd March 2016) - Yeung, June Chun; Lun, Vivian Miu-Chi
Abstract : Self-help materials inculcating individuals with positive self-statements are popular in recent years, although the effectiveness of such self-statements on improving individuals' psychological well-being has not yet been confirmed. Using a control-group pre-test/post-test design, we examined how positive self-statements may or may not benefit individuals' mood. Individual characteristics and modes of delivery were found to moderate mood changes resulting from positive self-statements. Specifically, we found that participants experienced negative mood change after reading positive self-statements, if they have low level of need satisfaction. However, we also found that participants experienced a mood boost after listening to positive self-statements, and this effect was unrelated to self-esteem or need satisfaction. These findings suggest that self-help materials with a focus on positive self-statements should be used with caution.